GENRE AND TASK BASED TEACHING IN A HOSPITALITY AND TOURISM TECHNICAL COURSE DURING THE PANDEMICS - SILVA DE AZEREDO , Luciana Aparecida; SOUTO GUIMARÃES ARAÚJO , Joana (Caminhos em Linguística Aplicada, 2025)
Abstract: This article aims at sharing our experience in English teaching at the integrated technical course in Hospitality and Tourism, at the Federal Center for Technological Education of Minas Gerais (CEFET- MG), during emergency remote teaching as a result of the covid-19 pandemic. The didactic sequence is presented in full, alongside, in general terms, the theoretical assumptions on which it was based. It involves teaching English ​​through discursive genres and task-based approach, as well as through an ESP perspective, since the course was directly related to the student’s area of professional interests and needs. Despite the difficulties regarding the chaotic context of the pandemics, the lack of equipment and/or internet access, the results obtained throughout the school year point to the student’s engagement and interest, as well as to reflection on their own teaching process and learning. Keywords: Hospitality and tourism technical course; ESP; Discursive genres; Task-based learning.